PEG2000‐DPSE‐coated quercetin nanoparticles remarkably enhanced anticancer effects through induced programed cell death on C6 glioma cells. Issue 11 (25th March 2013) - Wang, Gang; Wang, JunJie; Luo, Jie; Wang, Lei; Chen, XuanLi; Zhang, LiPing; Jiang, ShanQing
<x xml:space="preserve">Abstract</x> In this study, PEGylated nanoparticles quercetin drug delivery vehicles were investigated as carriers for anticancer drugs induced programed cell death (PCD). PEG2000‐DPSE‐coated quercetin nanoparticles were prepared and tumor cell killing efficacy was studied on glioma C6 cells and assayed for cell survival, apoptosis, or necrosis. The levels of ROS production and mitochondrial membrane potential (ΔΨm) were determined. Western blot assayed p53, p‐p53, cytochrome C, and caspase proteins expression were also studied. Results indicate that PEG2000‐DPSE‐QUE‐NPS showed dose‐dependent cytotoxicity to C6 glioma cells and enhanced ROS accumulation induced upregulation of p53 protein, which was accompanied with an increase in cytochrome c and caspase‐3 protein levels. These results support the hypothesis that quercetin nanoparticles‐coated PEG2000‐DPSE remarkably enhanced anticancer effect of induced programed cell death on C6 glioma cells. Overall, PEG2000‐DPSE‐coated quercetin nanoparticles showed promising potential as a drug carrier for cancer therapy. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 3076–3085, 2013.